2005
DOI: 10.1016/j.ejcts.2005.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Tirofiban and emergency coronary surgery

Abstract: The final common pathway of platelet aggregation leading to coronary thrombosis involves cross-linking of platelet receptor glycoprotein IIb-IIIa by primarily fibrinogen. Glycoprotein IIb-IIIa antagonists are being increasingly used as adjunctive therapy during percutaneous coronary intevention, and have shown to reduce the risk of death and myocardial infarction. However, a proportion of these patients continue to remain ischemic and present for emergency coronary grafting. The profound platelet inhibition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Another Canadian working group suggested that both eptifibatide and tirofiban have no increased risks for bleeding in comparison to abciximab in cases of urgent or emergent coronary surgery [11]. In contrast to our current findings Genoni and colleagues could not prove the benefit of stopping tirofiban therapy eight ours prior to surgery [12]. Of course, the risk for transfusion depends on several other factors, such as preoperative anemia, severely reduced left ventricular function or age, as already reported by the group around Litmathe [13].…”
Section: Lettercontrasting
confidence: 85%
“…Another Canadian working group suggested that both eptifibatide and tirofiban have no increased risks for bleeding in comparison to abciximab in cases of urgent or emergent coronary surgery [11]. In contrast to our current findings Genoni and colleagues could not prove the benefit of stopping tirofiban therapy eight ours prior to surgery [12]. Of course, the risk for transfusion depends on several other factors, such as preoperative anemia, severely reduced left ventricular function or age, as already reported by the group around Litmathe [13].…”
Section: Lettercontrasting
confidence: 85%
“…The authors hypothesize that platelet quiescence achieved with this shortacting drug could result in preserved platelet number and function, with improvement in hard clinical endpoints, without increasing bleeding rates. Similarly, reviewing the limited data on tirofiban and emergency coronary surgery, Shanmugam concludes that urgent revascularization can be safely performed in patients within a few hours of discontinuation of tirofiban with little added risk [32].…”
Section: Safety Of Cabg: Current Evidencesmentioning
confidence: 95%
“…It has a rapid onset and short duration of action after proper intravenous administration. Platelet activity returns to normal 4 to 8 hours after the drug is withdrawn (19). Eptifibatide (Integrilin) is the newer anti-platelet drug which inhibits the glycoprotein IIb/IIIa inhibitor.…”
Section: Glycoproteins Iib/iia Antagonistmentioning
confidence: 99%